Question
upstudy study bank question image url

Evaluate the integral. \[ \int_{1}^{2} \frac{4 y^{2}-2 y-12}{y(y+2)(y-3)} d y \]

Ask by Rose Reeves. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The integral evaluates to \( \frac{4}{5} \ln\left(\frac{8}{3}\right) \).

Solution

We wish to evaluate   I = ∫ from y = 1 to 2 of (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] dy. Step 1. Write the integrand in partial fractions. Assume that   (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] = A/y + B/(y + 2) + C/(y – 3). Multiply both sides by y(y + 2)(y – 3) to clear denominators:   4y² – 2y – 12 = A(y + 2)(y – 3) + B·y(y – 3) + C·y(y + 2). Step 2. Expand and Collect Like Terms. First, expand A(y + 2)(y – 3). Notice that   (y + 2)(y – 3) = y² – y – 6, so  A(y² – y – 6) = A·y² – A·y – 6A. Next, expand B·y(y – 3):   B·y(y – 3) = B·y² – 3B·y. Then, expand C·y(y + 2):   C·y(y + 2) = C·y² + 2C·y. Now, combine all the terms:   A·y² – A·y – 6A + B·y² – 3B·y + C·y² + 2C·y = (A + B + C)y² + (–A – 3B + 2C)y – 6A. Step 3. Equate coefficients with the numerator 4y² – 2y – 12:   Coefficient of y²: A + B + C = 4,   Coefficient of y: –A – 3B + 2C = –2,   Constant term: –6A = –12. From the constant term, solve for A:   –6A = –12 ⟹ A = 2. Now substitute A = 2 into the first equation:   2 + B + C = 4 ⟹ B + C = 2.                       (1) Substitute A = 2 into the y–coefficient equation:   –2 – 3B + 2C = –2 ⟹ –3B + 2C = 0 ⟹ 2C = 3B ⟹ C = (3/2)B.      (2) Now substitute (2) into (1):   B + (3/2)B = 2 ⟹ (5/2)B = 2 ⟹ B = (2·2)/5 = 4/5. Then, from (2), C = (3/2)(4/5) = 6/5. Thus, the partial fractions are:   (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] = 2/y + (4/5)/(y + 2) + (6/5)/(y – 3). Step 4. Integrate Term by Term. The integral becomes:   I = ∫ from 1 to 2 [2/y] dy + (4/5) ∫ from 1 to 2 [1/(y + 2)] dy + (6/5) ∫ from 1 to 2 [1/(y – 3)] dy. Each integral is a standard logarithmic form: • ∫ 1/y dy = ln |y| + C, • ∫ 1/(y + 2) dy = ln |y + 2| + C, • ∫ 1/(y – 3) dy = ln |y – 3| + C. Perform the integrations:   I = 2[ln |y|]₁² + (4/5)[ln |y + 2|]₁² + (6/5)[ln |y – 3|]₁². Evaluate each piece: 1. For 2[ln |y|] from 1 to 2:   = 2 (ln 2 – ln 1) = 2 ln 2   (since ln 1 = 0). 2. For (4/5)[ln |y + 2|] from 1 to 2:   = (4/5) (ln |2 + 2| – ln |1 + 2|) = (4/5)(ln 4 – ln 3). 3. For (6/5)[ln |y – 3|] from 1 to 2:   At y = 2, y – 3 = –1 (absolute value 1) and at y = 1, y – 3 = –2 (absolute value 2). Thus,   = (6/5)(ln 1 – ln 2) = (6/5)(0 – ln 2) = –(6/5) ln 2. Step 5. Combine the results. Add the contributions:   I = 2 ln 2 + (4/5)(ln 4 – ln 3) – (6/5) ln 2. Combine the ln 2 terms:   2 ln 2 – (6/5) ln 2 = (10/5 ln 2 – 6/5 ln 2) = (4/5) ln 2. Thus,   I = (4/5) ln 2 + (4/5)(ln 4 – ln 3)     = (4/5)[ln 2 + ln 4 – ln 3]. Recall that ln 2 + ln 4 = ln (2 · 4) = ln 8. Therefore, the answer is:   I = (4/5)[ln 8 – ln 3] = (4/5) ln(8/3). Final Answer:   ∫ from 1 to 2 (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] dy = (4/5) ln(8/3).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To evaluate the integral \[ \int_{1}^{2} \frac{4 y^{2}-2 y-12}{y(y+2)(y-3)} \, dy, \] we can start by performing partial fraction decomposition on the integrand. We want to express \[ \frac{4 y^{2}-2 y-12}{y(y+2)(y-3)} \] in the form \[ \frac{A}{y} + \frac{B}{y+2} + \frac{C}{y-3}. \] Multiplying through by the common denominator \(y(y+2)(y-3)\) gives us \[ 4y^2 - 2y - 12 = A(y+2)(y-3) + B(y)(y-3) + C(y)(y+2). \] Expanding each term on the right-hand side: 1. \( A(y+2)(y-3) = A(y^2 - y - 6) = Ay^2 + (2A - 3A)y - 6A = Ay^2 + (2A - 3A)y - 6A \) 2. \( B(y)(y-3) = By^2 - 3By \) 3. \( C(y)(y+2) = Cy^2 + 2Cy \) Combining all terms yields: \[ (A + B + C)y^2 + (2A - 3B + 2C)y - 6A = 4y^2 - 2y - 12. \] Now, we equate coefficients: - For \(y^2\): \(A + B + C = 4\) - For \(y\): \(2A - 3B + 2C = -2\) - Constant: \(-6A = -12\) or \(A = 2\) Plugging \(A = 2\) into the other equations gives: 1. \(2 + B + C = 4 \implies B + C = 2\) 2. \(2(2) - 3B + 2C = -2 \implies 4 - 3B + 2C = -2 \implies 2C - 3B = -6\) Now we solve the equations: From \(B + C = 2\), we can express \(C\) as \(C = 2 - B\). Substitute this into \(2C - 3B = -6\): \[ 2(2 - B) - 3B = -6 \implies 4 - 2B - 3B = -6 \implies -5B = -10 \implies B = 2. \] Thus, \(C = 2 - 2 = 0\). We have: \[ A = 2, \quad B = 2, \quad C = 0. \] Therefore, we can rewrite our integrand as: \[ \frac{4y^2 - 2y - 12}{y(y+2)(y-3)} = \frac{2}{y} + \frac{2}{y+2}. \] Now, we can rewrite the original integral: \[ \int_{1}^{2} \left( \frac{2}{y} + \frac{2}{y+2} \right) dy. \] Now we evaluate this: \[ \int_{1}^{2} \frac{2}{y} \, dy + \int_{1}^{2} \frac{2}{y+2} \, dy. \] 1. For the first integral: \[ \int \frac{2}{y} \, dy = 2 \ln |y| \Big|_{1}^{2} = 2 (\ln 2 - \ln 1) = 2 \ln 2. \] 2. For the second integral, use the substitution \(u = y + 2\): \[ \int \frac{2}{y+2} \, dy = 2 \ln |y+2| \Big|_{1}^{2} = 2 (\ln 4 - \ln 3) = 2\ln\left(\frac{4}{3}\right). \] Putting it all together gives: \[ 2 \ln 2 + 2 \ln \left(\frac{4}{3}\right) = 2 \left(\ln 2 + \ln \left(\frac{4}{3}\right)\right) = 2 \ln \left(\frac{8}{3}\right). \] Thus,

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy